Kemampuan Pemecahan Masalah Siswa SMA Kelas XI Pada Materi Lingkaran - Fadil Saputra; Suherman Suherman; Armiati Armiati (Program Studi Pendidikan Matematika, 2026)
Mathematical problem-solving skills is an important skill that students must possess because it can train critical, creative, and independent thinking in facing various problems. However, in reality, this skills is still not optimal, especially in solving problem-based problems. This study aims to analyze the skills of eleventh-grade students in solving mathematical problems related to the topic of circles, based on the stages of Polya's problem solving. This study used a descriptive quantitative approach. The research subjects consisted of 47 grade XI students from two classes. Data were collected through a mathematical problem-solving skills test and analyzed using descriptive statistics. The results of the study indicate that students' mathematical problem-solving skills are generally still relatively low. As many as 43.8% of students are in the low category and 39.6% are in the very low category. Based on the analysis of each indicator, students are relatively more capable at the stage of understanding the problem, while the greatest difficulties are found at the stage of planning the solution and reviewing the results of the solution.